Systolic Blood Pressure Variability When Transitioning From Intravenous to Enteral Antihypertensive Agents in Patients With Hemorrhagic Strokes - Alshaya, Abdulrahman I.; Alghamdi, Meshari; Almohareb, Sumaya N.; Alshaya, Omar A.; Aldhaeefi, Mohammed; Alharthi, Abdullah F.; Almohaish, Sulaiman (Frontiers in Neurology, 2022)
Background/Objective Systolic blood pressure variability (SBPV) in patients with intracranial hemorrhage (ICH) and subarachnoid hemorrhage (SAH) is associated with an increased risk of acute kidney injury (AKI) and mortality. SBPV is a strong predictor of poor functional outcomes in patients with ICH. Intravenous (IV) antihypertensive agents are commonly used to achieve sustained target blood pressure goals; however, this is not a feasible long-term option. The transition from IV to enteral antihypertensives is not yet well established in patients with ICH and SAH. This study aimed to assess the effect of the number of antihypertensive agents and overlap time during the transition period from IV to enteral route on SBPV in patients with ICH and SAH. Methods This retrospective single-center study was conducted at a tertiary teaching hospital in Riyadh, Saudi Arabia. Data were extracted from electronic medical records after obtaining Institutional Review Board approval. Patients were included if they were >18 years old, admitted with spontaneous ICH or SAH, and received continuous infusion antihypertensives prior to transitioning to the enteral route. The major outcome was the effect of the number of antihypertensive agents and overlap time on SBPV during the transition process. Minor outcomes included the effect of the number of antihypertensive agents and overlap time on heart rate variability and the incidence of AKI on day 7. Results After the screening, we included 102 patients. Based on our regression model, the number of enteral antihypertensive agents upon transitioning from IV to enteral antihypertensive therapy had no effect on SBPV in the intensive care unit (ICU) among our patients (p-value = 0.274). However, the prolonged overlap was associated with reduced SBPV in the ICU (p-value = 0.012). No differences were observed between the groups in heart rate variation or AKI rate. Conclusions In patients with ICH and SAH, prolonged overlap of enteral antihypertensive agents to overlap with intravenous antihypertensive therapy may result in lower SBPV. This finding needs to be confirmed on a larger scale with more robust study designs for patients with ICH and SAH.